Organic matter: a critical soil health indicator in agrosystems within the Cerrado of Bahia, Brazil and South Florida, USA - Santos, Flávia Cristina dos; Albuquerque Filho, Manoel Ricardo de; Soares, Johnny Rodrigues; Jesmin, Tanjila; Manirakiza, Noel; Silveira, Márcia Cristina Teixeira da; Mendes, Ieda de Carvalho; Oliveira, Maria Ines Lopes de; Melkani, Suraj; Freitas, Antonio Carlos Reis de; Malaquias, Juaci Vitoria; Bhadha, Jehangir H. (Frontiers in Soil Science, 2025)
Soil health (SH) indicators, such as organic matter (OM) content and enzymatic activity (EA), are critical for assessing the sustainability of mineral soils in integrated and cover cropping systems. Taking into account the following objectives: (i) to assess the relationship between OM and other SH indicators, (ii) to evaluate the evolution of SH using two models (SH indicators (SHI) scoring approach and A Modified Comprehensive Assessment of Soil Health scoring system developed for Florida soils (A modified CASH method)), and (iii) present their effectiveness in Brazil and the USA, a medium-term study (2019–2023) in Brazil and a short-term seasonal study (2022–2023) in the USA were conducted in diverse agroecosystems. In Brazil, four agricultural systems were analyzed: Cerrado (Cer), Conventional (Conv), Integrated Crop-Livestock (ICL), and Integrated Crop-Livestock-Forestry (ICLF). In the USA, two cover cropping systems in South Florida were assessed: double cover cropping system (DCCS) and multiple cover cropping system (MCCS). Soil samples were collected for analysis of key soil properties. Results in Brazil showed higher OM in the Cer (1.08 dag kg-1) and ICL (1.12 dag kg-1) systems, and increased enzymatic activity in 2023, particularly in ICL (AS = 33.85 mg de p-nitrofenol kg-1 soil h-1 and BG = 54.65 mg de p-nitrofenol kg-1 soil h-1) and ICLF (AS = 21.07 mg de p-nitrofenol kg-1 soil h-1 and BG = 48.90 mg de p-nitrofenol kg-1 soil h-1). Enzyme activity was more responsive to management practices than OM. Principal Component Analysis revealed stronger correlations between OM, EA, and macronutrients in more sustainable systems like ICL and ICLF. The SHI scoring approach better captured changes in Brazil. In the USA short-term cover cropping systems showed no significant changes in OM or EA, but CASH method suggested slight improvements in MCCS. This study highlights the importance of OM and EA as key indicators for assessing and improving SH and suggests that while integrated and cover cropping systems offer potential benefits, longer-term management and organic amendments are necessary to achieve sustained improvements in soil health.